Clinical Evaluation of Using Etch and Rinse and Self- Etch Adhesive Systems on Primary Molars - Mohamed K. Al-Tinawi; Arwa M. Khir; Hala A. Al-Edlebi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Dentin bonding systems are available as three, two and one step systems, depending on how these etching, priming and bonding steps have done. The objective of this study is to evaluate the clinical outcomes of composite restorations performed on primary molars using self-etch and etch & rinse adhesive systems over one year. Twenty eight children ages 7-9 years old; with class II carious lesions on their lower second molars have been enrolled in this study. All molars (56) were restored by composite (Tetric Evo Ceram, Ivoclar Vivadent). Self-etch (AdheSE One F, Ivoclar Vivadent), and etch & rinse (ExciTE, Ivoclar Vivadent) adhesive bonding systems were used. Clinical evaluation has been performed according to Modified United States Public Health Service criteria at baseline, after 3, 6, and 12 months. Results were analyzed using Mann-Whitney U test. There were no significantly statistical differences (P < 0.05) in the clinical evaluation at (base line, 3, 6, and 12 months) between two groups. The class II composite restorations have shown to be satisfactory for two kind of dentin bonding systems. It would be useful to use self-etch adhesive bonding systems with children to shorten the processing time.